Vestibuloplasty with Retroauricular Skin Grafts for Dental Implant Rehabilitation in Vascularized Fibula Grafts: Two Case Reports - VAROL, ALTAN (QUINTESSENCE PUBLISHING CO INC, 2017)
The aim of this study was to present the use of retroauricular full-thickness skin grafts in vestibuloplasty surgeries for dental implant rehabilitation in vascularized fibula grafts. Two patients underwent mandibular reconstruction with vascularized fibula grafts due to mandibular gunshot injuries. Inadequate sulcus gaps secondary to mandibular soft tissue deficiencies were managed by full-thickness autologous skin grafts harvested from the retroauricular region. Dental rehabilitation was achieved by implants placed in free fibula grafts. In both cases, complete graft survival was achieved. Cosmetic and functional outcomes were satisfactory. Owing to its high resiliency and elasticity and its thin and hairless structure, full-thickness retroauricular skin graft is an effective treatment modality in the management of intraoral soft tissue deficiencies. Patients with gunshot injuries present great functional and esthetic demands, and every report presenting new treatment modalities is helpful in the management of the condition.
Keywords: COMPOSITE MANDIBULAR DEFECTS; PARTIAL-THICKNESS SKIN; SOFT-TISSUE; RECONSTRUCTION; FLAP; MODEL; FULL